FACTORS THAT INFLUENCE THE DECISION OF INTERNATIONAL STUDENT MOBILITY - Estela Maricela Villalón de La Isla; Antonio Humberto Closas; Antonio Luzón Trujillo (Revista de la Facultad de Ciencias Económicas, 2018)
Mobility is one of the main strategies of the internationalization process of the University of Guadalajara (UdeG), which it is of transcendental importance to know the perception of its students about the factors that influence the decision to study, or not, a semester in another country. This study analyzes the motivation and attitude of 126 undergraduate and graduate students regarding the possibilities of international mobility, from their perspective. The sample of participants is made up of active students enrolled in one of the Regional Centers that make up the University Network of UdeG, the University Center of the North (CUNorte), located in the city of Colotlán, Jalisco, Mexico. Understood student mobility as one of the fundamental strategies in the process of internationalization of Higher Education, this work contributes to the strengthening of research on issues that affect the achievement of objectives marked in the thematic axis of internationalization of the current Development Plan of the University Center.